Simultaneous Saccharification and fermentation process of bioethanol from palm oil empty fruit bunches - Eryati Derman (2018)
Currently, new renewable energy resources are seek out to substitute fossil fuels in the transportation sector in order to tackle the increasing energy demand. Bioethanol emerge as a potential option in replacing transportation fuels of gasoline. Oil palm empty fruit bunches (EFBs) are one of the promising biomass wastes, which can be utilized as a feedstock for the second generation bioethanol production. Optimal conditions are required for a cost-efficient bioethanol fuel processesfr om EFBs.T hus, this study aims to optimize the processc onditionsf or bioethanol production from EFBs through simultaneous saccharification and fermentation( SSF)p rocessu sing ResponseS urfaceM ethodology( RSM).T his study can be divided into two main parts which are the screening of the optimum concentration of enzymes and microorganisms and optimization of fermentation parameters. In this study, EFBs were treated using sequential acid and alkali treatment before being used as substrate. Physical morphologies and structures of the EFBs were analyzed using Scanning Electron Microscope (SEM) and Fourier Transform Infrared (FTIR). The findings revealed that the pretreatment has changed the morphology and EFBs structure by removing silica which act as the chemical composition barrier that causes pores formation. In the first part of this study, the optimum combination of enzymes and microbes for bioethanol production was screened. According to the results, co-cultures of S. cerevisiae and T harzianumc ombinedw ith Cellulasea nd (3-glucosidaswe as selectedf or further used in the fermentation steps. This combination produced the highest bioethanol concentration determined at 11.76 mg/mL. Under optimal conditions for enzymatic saccharification, 4% (w/v) of pretreated EFB was completely hydrolyzed and produced 21.14 ± 1.49 mg/mL glucose at 50 °C, 150 rpm and 72 hours operating conditions. In the second part in this study, Central Composite Design of RSM was employed to optimize the SSF process including the fermentation time, temperature, inoculum concentration, and pH. It was found that fermentation for 72 hours duration, 30 °C and pH 4.8 of media using 6.79% (v/v) of inoculum concentration could produce up to 9.72 mg/mL of bioethanol and 0.46 g/g glucose of bioethanol yield with 90.63% conversion efficiency. Fermentation conducted under optimum conditions yielded 9.65 mg/mL of bioethanol, 0.46 g/g glucose of bioethanol yield and 89.56% conversion efficiency which were in close agreement with the model suggested. Overall, this study showed better results for bioethanol production as compared to previous research done using EFBs as the feedstocks